Measuring shaming in an ethnic context - Zhang, Sheldon (The British journal of criminology, 1995)
This study was an attempt to operationalize John Braithwaite's theory of reintegrative shaming, and measure how it is used by parents of different ethnic groups in response to their delinquent children. Based on Braithwaite's emphasis on interdependency, familism, and communitarianism in certain Asian cultures, it was hypothesized that Asian-Americans would be more likely to use shaming as a parenting practice than would African-Americans. The findings showed that the two ethnic groups differ significantly only in verbal shaming; not in non-verbal, physical, or communitarian shaming as measured here. However, when marital status was controlled, ethnicity appeared to have no effect on shaming. Married parents were significantly more inclined to shame their delinquent children than single parents regardless of their ethnicities. New Asian immigrant parents were also more likely to shame than others